Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/brb3.624
|View full text |Cite
|
Sign up to set email alerts
|

CADASIL: Ultrastructural insights into the morphology of granular osmiophilic material

Abstract: IntroductionCerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a hereditary systemic vascular disorder. Granular osmiophilic material (GOM) is its ultrastructural marker. We reviewed tissue biopsies from CADASIL patients to establish whether ultrastructural observations help clarify the pathogenic mechanism of CADASIL. Given the resemblance of the GOM deposits to the immunoglobulin deposits seen in glomerulonephritis and focal segmental glomerulosclerosis (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Electron microscopy analysis on skin, skeletal muscle, kidney, and pericardial samples of CADASIL patients identified GOMs not only around VSMCs and pericytes of the brain, but also in the above-mentioned tissues, supporting the idea that CADASIL is a systemic disease and not only a disorder confined to the CNS (Lewandowska et al, 2010;Morroni et al, 2013). Moreover, Lorenzi et al found that several GOM deposits were surrounded by an electron-lucent halo, probably made of more densely packed extracellular matrix around the GOM which interferes with ubiquination and transendocytosis of mutant NOTCH3, preventing GOM clearance and promoting protein accumulation (Lorenzi et al, 2017). Therefore, the halo around GOMs may represent the morphological evidence of aberrant NOTCH3 processing, and could be considered as an ultrastructural marker for CADASIL (Lorenzi et al, 2017).…”
Section: Histopathological Findingsmentioning
confidence: 82%
See 1 more Smart Citation
“…Electron microscopy analysis on skin, skeletal muscle, kidney, and pericardial samples of CADASIL patients identified GOMs not only around VSMCs and pericytes of the brain, but also in the above-mentioned tissues, supporting the idea that CADASIL is a systemic disease and not only a disorder confined to the CNS (Lewandowska et al, 2010;Morroni et al, 2013). Moreover, Lorenzi et al found that several GOM deposits were surrounded by an electron-lucent halo, probably made of more densely packed extracellular matrix around the GOM which interferes with ubiquination and transendocytosis of mutant NOTCH3, preventing GOM clearance and promoting protein accumulation (Lorenzi et al, 2017). Therefore, the halo around GOMs may represent the morphological evidence of aberrant NOTCH3 processing, and could be considered as an ultrastructural marker for CADASIL (Lorenzi et al, 2017).…”
Section: Histopathological Findingsmentioning
confidence: 82%
“…Moreover, Lorenzi et al found that several GOM deposits were surrounded by an electron-lucent halo, probably made of more densely packed extracellular matrix around the GOM which interferes with ubiquination and transendocytosis of mutant NOTCH3, preventing GOM clearance and promoting protein accumulation (Lorenzi et al, 2017). Therefore, the halo around GOMs may represent the morphological evidence of aberrant NOTCH3 processing, and could be considered as an ultrastructural marker for CADASIL (Lorenzi et al, 2017). However, GOM formation and development over time and their role in disease progression remain largely unknown.…”
Section: Histopathological Findingsmentioning
confidence: 99%
“…Thus, patient with sister were directed to Institute Psychiatry and Neurology in Warsaw to perform myo-cutaneous biopsy. In this test presence of granular osmophilicmaterial (GOM) was confirmed in patient and her sister [3]…”
Section: Case Reportmentioning
confidence: 82%
“…GLUT1 is the major glucose transporter in ECs, and its expression level is decreased in CADASIL as shown in brain biopsy studies ( Giwa et al, 2012 ; Craggs et al, 2013 ; Craggs et al, 2015 ). Since GLUTs are expressed in VSMC of systemic organs, and there are few studies that indicate that the VSMC of other organs are bear GOM deposits in CADASIL subjects ( Lorenzi et al, 2017 ) and that endothelium-dependent vasodilation is impaired in forearm resistance arteries ( Stenborg et al, 2007 ) it is not unlikely that GLUT4 and -2 are affected in other organs of CADASIL patients. We were not able to analyze GLUTs in other organs VSMC due the unavailability of systemic tissues.…”
Section: Discussionmentioning
confidence: 99%